Analysis of the Relationship Between Knowledge and Supervision with Use of Personal Protective Equipment (PPE) at PT.PLN (persero) ULP SOe - Nelsin Sete; Noorce Ch Berek; Mustakim Sahdan (Lontar : Journal of Community Health, 2022)
There are several ways to control the risk of hazards in the workplace, one of which is the use of PPE. PPE is equipment that must be used when working according to work hazards and risks to maintain the safety of the workers themselves and those around them. Although the use of personal protective equipment is at the last level of control, use of personal protective equipment is highly recommended. PPE is personal protective equipment, namely equipment that must be used to protect workers from hazards that can cause serious injury or illness. This study aims to analyze the relationship between knowledge and supervision with the use of personal protective equipment at PT. PLN (Persero) ULP Soe. The type of research used is an analytic survey with a cross-sectional design. The sample of this research is 30 people from the field team of PT. PLN (Persero) ULP Soe. Data was obtained by questionnaires and observations. The data analysis used is a univariate and bivariate analysis using the chi-square test. The results of research at PT. PLN (Persero) ULP Soe shows that knowledge has a relationship with the use of PPE with a p-value = 0.001, and supervision has a relationship with the use of personal protective equipment with a value = 0.010). Suggestions for field team workers are related to the use of personal protective equipment, with training and encouragement for all workers to use personal protective equipment so that implementation in the workplace can be realized properly. Keywords: personal protective equipment, field team, knowledge, supervision